10.1111/acn.v9999.9999 (CrossRef Listing of Deleted DOIs, 2000)
OBJECTIVE: This study evaluated demographic, clinical and perceptual factors associated with enrolment in a Phase III transoral surgical trial for HPV-related oropharyngeal carcinoma. DESIGN: Single-centre, questionnaire-based cross-sectional pilot study of patients screened for PATHOS trial. SETTING: Tertiary cancer centre participating in the PATHOS trial. PARTICIPANTS: Patients with p16-positive oropharyngeal carcinoma were eligible for the trial. Of 100 patients screened, 70 met trial eligibility and 51 completed a telephone questionnaire and were included. Inability to complete the questionnaire because of cognitive impairment or a language barrier was a prespecified survey exclusion criterion. However, no patient was excluded for either reason. MAIN OUTCOME MEASURES: Primary outcome was the patient decision to enrol or decline participation in PATHOS (written consent). Predictor variables included demographic and clinical characteristics and responses to a 31-item Likert-scale questionnaire. RESULTS: Among 51 eligible patients who completed the questionnaire, 29 (57%) enroled in the trial. On univariable analysis, significant predictors included perceptions of treatment quality, toxicity, quality of life, travel distance, trial comprehension, randomisation, medical terminology, trust, prior trial experience and concern about being treated as a 'guinea pig'. On multivariable analysis, prior trial experience (p = 0.022) and not feeling like a 'guinea pig' (p = 0.047) remained significant, with travel distance trending (p = 0.087). CONCLUSIONS: Trial enrolment was driven primarily by prior exposure to clinical research and perceptions of vulnerability and trust, rather than by demographic or tumour factors. Addressing fears of being a 'guinea pig', improving trial comprehension and mitigating travel-related barriers may enhance accrual and promote more equitable participation in head and neck cancer trials.